STRATEGI KOPERASI DALAM MENINGKATKAN KESEJAHTERAAN ANGGOTA - Muhammad Syaiful, Muhammad Syaiful (Pascasarjana Universitas Halu Oleo, 2016)
The problems addressed by this study were: (1) how are strategies implemented by Koperasi Kesejahteraan Bersama of FKIP UHO to improve the welfare of its members; (2) what are the hindrances encountered by Koperasi Kesejahteraan Bersama of FKIP UHO in its effort to improve the welfare of its members; (3) what strategies are employed by Koperasi Kesejahteraan Bersama of FKIP UHO to overcome the hindrances that it encounters in its effort of improving the welfare of its members. The purpose of this study was to reveal: (1) the strategies that were implemented by Koperasi Kesejahteraan Bersama of FKIP UHO to improve the welfare of its members; (2) the hindrances encountered by Koperasi Kesejahteraan Bersama of FKIP UHO in its effort of improving the welfare of its members; (3) the strategies are employed by Koperasi Kesejahteraan Bersama of FKIP UHO to overcome the hindrances that it encounters in its effort of improving the welfare of its members. Techniques of data collection were interview, observation, and documentation. Data were analyzed qualitatively, namely data reduction, data presentation, and drawing of conclusions. Results of the study were: the strategies that were implemented by Koperasi Kesejahteraan Bersama of FKIP UHO to improve the welfare of its members were: (1) increasing member contributive participation by raising understanding about the importance of participating in the cooperation to the members themselves, transparency, honest, open, whereas incentive participation was increased by lowering interest rate and granting presents on lebaran day; (2) increasing service to its members by requiring nothing at all to those who wish to loan money, providing out-of-office services, and if a member wants to fully return his loan earlier than the contract, he does not need to pay the remaining interests. (3) increasing the cooperation capital by increasing members’ compulsory deposit and SHU to be received by members is not directly paid, but deposited in a special saved SHU. Some hindrances faced by Koperasi Kesejahteraan Bersama of FKIP UHO are related to limited capital and bad credit. Strategies employed by Koperasi Kesejahteraan Bersama are directly informing its members about bad credit, increasing compulsory deposit in order to increase the cooperation capital so that the problem of capital can be solved. Keywords: cooperation strategies, members’ welfare